Mainstreaming Religious Moderation within the Three Pillars of Islamic Higher Education in East Java - Feryani Umi Rosidah,; Syafi’i, Imam; Basyir, Kunawi (Empirisma: Jurnal Pemikiran dan Kebudayaan Islam, 2025)
The implementation of religious moderation in Islamic Higher Education Institutions (PTKI) in East Java represents a strategic effort to develop a balanced and inclusive understanding of religion. This research was conducted at the State Islamic Institute of Kediri, the Islamic University of Malang, and the Muhammadiyah University of Surabaya. The article aims to analyze the application of religious moderation through the Three Pillars of Higher Education, namely teaching, research, and community service. The study employs a qualitative approach, using in-depth interviews and participatory observation involving students, lecturers, as well as faculty and rectorate leaders. The findings reveal that the values of religious moderation are integrated into teaching and curriculum through courses such as Interreligious Dialogue, Multiculturalism, workshops, and inclusive seminars. In the field of research, moderation is reflected in scholarly studies addressing diversity and tolerance. Meanwhile, in community service, it is manifested through community service programs (KKN), interfaith dialogues, and multicultural empowerment initiatives. This study recommends the development of strategic policies based on religious moderation to cultivate an inclusive and contextual generation capable of responding to the challenges of globalization and radicalism in the modern era.